Resistência e reafirmação camponesa: transformações e permanências na agricultura no município de Faina/GO - Silva, Aelton Brito [UNESP] (2014)
This thesis analyzes the forms of resistance that small farmers in the municipality of Faina / GO have developed to withstand transformations stimulated by policies of agricultural modernization since the 1970s. The study uses a comparative approach to chart production and lifestyle transformations between two generations of peasant families in Faina, a small rural community located near the historic colonial city of Goiás Velho. It argues that modernization policies have provoked transformations in production processes and the relations of production, thus altering the way of life of peasant farmers and the composition of their territory. In addition to bibliographical and documentary research, a geo-historical questionnaire was used to generate data from affected families. Responses were gathered through interviews, which also stimulated the collection of oral histories, covering seven peasant families organized in the municipality by the Movement of Small Farmers - MPA, which has worked to reaffirm their peasant identity